Influencing Factors Led Local Consumer’s Bang Sue District Revisits to Shopping Mall nearby: A Comparison between Wongsawang Shopping Mall and Gateway at Bang Sue - Sitthichaiyakul, Sarut; Hunnimitr , Pimchanok; Liu, Jiaji; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – This research aims to analyze the influencing factors that lead local consumers in the Bang Sue district to revisit nearby shopping malls: a comparison between Wongsawang Shopping Mall and Gateway at Bang Sue. Design/Methodology/Approach – The study employs both primary and secondary data collection methods to analyze the factors influencing local consumers’ revisits to shopping malls in the Bang Sue district. The data were gathered from 394 respondents residing in Bang Sue district, expressing a desire to revisit Wongsawang shopping mall and Gateway at Bang Sue. The research incorporates three theoretical frameworks from previous studies to create a new conceptual framework. Findings – The research investigates the factors influencing residents of Bang Sue to revisit nearby malls, highlighting the significant impact of mall atmosphere on the overall mall experience and the influence of retail tenant mix. Mall experience, in turn, significantly affects the likelihood of revisiting a shopping mall, while the retail tenant mix has a notable influence on local consumers in the Bang Sue district revisiting nearby shopping malls. Research Limitations/Implications – The study underscores the significance of overall shopping mall factors in influencing customers to revisit nearby malls. A positive environment, encompassing aesthetics, cleanliness, lighting, and amenities, plays a crucial role. While tenant mix may not directly impact the mall experience, it remains vital for overall attractiveness. Limitations include a focus on revisiting customers in the Bang Sue district, potentially limiting generalizability to different locations and types of malls. Geographical and spatial differences may influence customer decision-making when revisiting malls. Keywords: Mall Perception, Mall Atmosphere, Retail Tenant Mix, Mall Experience, Revisit Shopping Mall JEL Classification Code – L81, L85, M20, M30